Analysis of Gender Diversity in the Board of Commissioners and Its Influence on the Profitability of State-Owned Enterprises (SOEs) in Indonesia - Budi Rustandi Kartawinata; Diki Wahyu Nugraha; Aznul Fazrin Abu Sujak (Government & Resilience, 2026)
This study examines the association between gender diversity on the Board of Commissioners and the financial performance of Indonesian State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) over the 2020–2024 period. Grounded in Resource Dependence Theory and Agency Theory, a quantitative explanatory approach was applied to a balanced panel dataset of 125 observations from 26 SOEs. Profitability was proxied by Return on Assets (ROA), while firm size, leverage, and firm age served as control variables. Panel data regression using the Fixed Effects Model (FEM) was employed, with robust standard errors clustered at the firm level. The results reveal that gender diversity—specifically the proportion of female commissioners—has a statistically significant positive association with ROA (β = 1.7654, p < 0.05), whereas the dummy variable for the mere presence of women is positive but not statistically significant (p = 0.063). This finding suggests that the extent of female representation matters more than token presence. The study concludes that gender diversity in Indonesian SOEs is not merely a compliance mechanism but is positively associated with enhanced profitability. However, given the observational design and potential endogeneity concerns (Durbin-Wu-Hausman test p = 0.233), findings are reported as associations rather than causal effects. These results offer critical insights for policymakers in emerging markets to evaluate the effectiveness of gender diversity mandates beyond formalistic tokenism and provide a foundation for future research exploring mediating mechanisms such as board dynamics and risk committee effectiveness.